The effect of parental attitudes on habilitation of hearing impaired children - Ristić Snežana; Kocić Biljana; Milošević Zoran (Vojnosanitetski Pregled)
Background/Aim. Habilitation of children with hearing loss is a very complex process and requires a team work. Habilitation period length, as well as the effects themselves are individual and depend on many factors. The goal of any habilitation process is to improve the quality of life of each individual to the maximal extent possible, regardless of whether embedded cochlear implant, or other forms of amplification applied. A long-standing practice has shown that the influence of parents and their attitudes in the habilitation process is great. The aim of this study was to examine the extent of this influence in order to educate the parents so to help their children maximize their potential. Methods. The instruments used in this study were: semi-structured interview, the Parental Attitudes Scale (PAD), Package Nottingham Early Estimates (NEAP). The participants in this study were the parents with children aged 4-15 years. The extent of hearing loss in the children was recorded at the beginning and during the habilitation process and all were actively involved at least three months. For statistical analysis of this study the descriptive and inferential statistical techniques were applied. Results. The results of our study show significant differences in certain parental attitudes. A close cooperation of the parents and quality experts interactions with the parents are a prerequisite for a successful habilitation. Conclusion. The result of this research show that the process of habilitation of children with hearing and speech disorders is significantly affected by the parent attitudes. Parental attitudes were proved to be especially important for children with greater hearing loss. It was also noted that in our society mainly mothers are concerned with hearing-damaged children, which indicates that the educational process should be extend to both parents.